2021
DOI: 10.3389/fonc.2021.619013
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RhoV Promotes the Progression and EGFR-TKI Resistance of Lung Adenocarcinoma

Abstract: BackgroundThe Rho GTPase family with ~20 member genes play central roles in a wide variety of cellular processes and tumor cell migration and metastasis. Different Rho GTPase may play different roles in the progression of lung adenocarcinoma.MethodsWe comprehensively examined the expression of all Rho GTPase family member genes in a panel of lung adenocarcinoma patient’s tumors and matched normal tissues. We next investigated the critical role of RhoV in different lung adenocarcinoma cells and animal models.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Based on the study by Zhang et al, the RAS homologous family member V (RHOV) is majorly involved in LUAD metastasis and may provide biomarkers for prognosis prediction and LUAD treatment [ 43 ]. Other research has found that overexpression of RhoV in lung adenocarcinoma promotes lung adenocarcinoma occurrence and progression, as well as EGFR-TKI resistance [ 44 ]. CPS1 (carbamoyl phosphate synthase 1) is a rate-limiting enzyme in the first step of the urea cycle and is also required for human liver metabolism [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study by Zhang et al, the RAS homologous family member V (RHOV) is majorly involved in LUAD metastasis and may provide biomarkers for prognosis prediction and LUAD treatment [ 43 ]. Other research has found that overexpression of RhoV in lung adenocarcinoma promotes lung adenocarcinoma occurrence and progression, as well as EGFR-TKI resistance [ 44 ]. CPS1 (carbamoyl phosphate synthase 1) is a rate-limiting enzyme in the first step of the urea cycle and is also required for human liver metabolism [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…RHOV has been shown to promote cell differentiation and act as an important regulator of neural crest induction ( Guémar et al, 2007 ; Song et al, 2015 ). RHOV is highly expressed in many lung cancer cell lines and promotes the growth and metastasis of LUAD cells ( Zhang Y. et al, 2020 ; Chen H. et al, 2021 ; Zhang et al, 2021 ). CYP4B1 belongs to the mammalian CYP4 enzyme family and is mainly expressed in human lungs ( Wiek et al, 2015 ).…”
Section: Discussionunclassified
“…For instance, ANLN is a well-known oncogene that promotes carcinogenesis and therapeutic resistance in multiple types of cancers, such as LUAD ( Long et al, 2018 ; Xu et al, 2019 ; Deng et al, 2021 ), oral cancer ( Wang B et al, 2021 ), colorectal cancer ( Liu et al, 2022 ), breast cancer ( Wang et al, 2020 ; Maryam and Chin, 2021 ), pancreatic cancer ( Wang et al, 2019 ), and head and neck squamous cell carcinoma ( Guo et al, 2021 ). RHOV has been widely studied to promote LUAD cell growth, metastasis, and therapeutic resistance ( Chen H et al, 2021 ; Zhang et al, 2021 ). In addition, KRT6A has been shown to participate in tumor proliferation, invasion, EMT, and cancer stem cell transformation in lung cancer ( Yang et al, 2020 ; Zhou J et al, 2021 ; Che et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%